Penguasaan Kosakata Bahasa Indonesia Siswa SD Ditinjau dari Aspek Kelas Kata: Studi Kasus pada Tiga Sekolah Dasar di Kota Ternate, Provinsi Maluku Utara - Sri Winarti (Tematik: Jurnal Penelitian Pendidikan Dasar, 2023)
This paper examines the vocabulary mastery of Indonesian elementary school students in the city of Ternate. The problem in this study is formulated in the question, how is the mastery of Indonesian vocabulary by elementary school students in Ternate city? This study aims to determine the vocabulary mastery of Indonesian elementary school students in the city of Ternate, North Maluku Province. The method used in this study is the survey method, which is a research method that takes samples from the population and collects data through questionnaires as the main data collection tool. The findings obtained in this study are that the level of mastery of Indonesian vocabulary by elementary school students in Ternate is classified in the poor category. On average, elementary school students in Ternate do not master Indonesian vocabulary. In this study, there are seven aspects of word class as seen from the level of vocabulary mastery, namely nouns, verbs, adjectives, prepositions, adverbs, pronouns, and numerals. If viewed from the word class, the mastery of Indonesian vocabulary in the categories of prepositions, adverbs, and pronouns is quite mastered by elementary school students, while the mastery of vocabulary in the categories of nouns, verbs, adjectives, and numerals is not mastered by elementary school students.